Antioxidative, antikinase or antiphosphatase and antimicrobial activities of selected vegetables in Sabah, Malaysia - Adznila Eberahim (2014)
Vegetables offer various health benefits to humans. However, there is a lack of investigation on the biological activities of these vegetables especially vegetables originating from Sabah. Thus, fifty two species of vegetable samples were collected from local markets in Sabah and were screened for their antioxidant activity using DPPH• assay. Five samples with high DPPH• scavenging activity ranging from 84.32% to 94.72% were selected for further study which were Cosmos caudatus, Eryngium foetidum, Ipomoea batatas, Ipomoea batatas var. green star shaped leaf and Manihot esculenta Crantz. These five samples were subjected to different solvent extractions (air-dried sample) and different cooking methods (raw sample). All of these extracts exhibits antioxidant activities ranging from 3.52% to 92.22% for all of the three antioxidant assays (DPPH•, O2• and NO• scavenging assays). Boiled water extracts of I. batatas var. green star shaped leaf and M. esculenta Crantz exhibits high antioxidant activity compared to the other solvent extractions whereas steaming and microwave cooking extracts of I. batatas var. green star shaped leaf and M. esculenta Crantz, respectively exhibits high antioxidant activity compared to the other cooking methods. Neither of the single solvent extractions or cooking methods extracts of C. caudatus and I. batatas that exhibits high antioxidant activity. In addition to that, steaming cooking extracts of E. foetidum was the only extract with high antioxidant activity. None of these extracts were exhibiting inhibition activity against GSK-3β screening test whereas there were two extracts that exhibits toxic activity against MKK1 and MSG5 screening test. These extracts were raw sample of I. batatas and I. batatas var. green star shaped leaf. Antikinase or antiphosphatase activities of these extracts were 9.33 mm (glucose media) for MKK1 whereas ranging from 7.67 mm to 8 mm (glucose media) and 8 mm to 8.33 mm (galactose media) for MSG5 screening tests. Among nine microbial strains that were tested, only two bacterial strains were inhibited by almost all of these extract which were Staphylococcus aureus and Pseudomonas aeruginosa. The antibacterial activities of these extracts were ranging from 6.67 mm to 16 mm. Raw samples of I. batatas and I. batatas var. green star shaped leaf exhibits the largest inhibition activity against S. aureus (10 mm) and P. aeruginosa (16 mm), respectively. Proximate analysis test results showed that E. foetidum has the highest moisture (87.57%) and protein contents (17.29 mg/mL) whereas M. esculenta Crantz has the highest ash content (4.11%) compared to the other vegetable species. Furthermore, I. batatas have the highest fat content (1.08%).